Familial hypercholesterolemia. Perspectives on FH registry systems - Pavlatou, Niki; Kadda, Olga; Marvaki, Christina; Kolovou, Genovefa (Health & Research Journal, 2022)
Familial Hypercholesterolemia (FH) is a genetic cause of premature Cardiovascular Disease (CVD) which is the leading cause of morbidity and mortality worldwide. In Greece, it is estimated that 90% of patients remain undiagnosed. Patients with FH are at high risk for cardiovascular events, peripheral arterial disease, stroke and death at a young age. Therefore, early detection of these is important for the implementation of appropriate preventive measures. Patient medical records are a powerful tool for recording and monitoring the disease and promoting clinical practices, thus helping to improve outcomes and reduce the cost of healthcare. Simultaneously with the registers, patient-centered management, multidisciplinary teamwork, involvement of primary care physicians, patient networks and support teams are required. Of most importance is the Greek online register system of people with familial hypercholesterolemia, by the Hellenic Atherosclerosis Society in collaboration with major hospital centers and the Hellenic College of Atherosclerosis Treatment registration system in the community. The purpose is to find people who are suffering from FH, to diagnose, to educate them and to put them under treatment and follow-up. In conclusion, effective care of patients with dyslipidemia requires: a) detailed evaluation of medical history, b) clinical and laboratory tests, and c) patient education programs regarding lifestyle changes and disease management. The above strategies of care will help reduce time and cost of medical treatment, obtain better clinical outcome and improve patients’ quality of life.